Double stent assisted coiling of intracranial bifurcation aneurysms in Y and X configurations with the Neuroform ATLAS stent: immediate and mid term angiographic and clinical follow-up. (27th July 2019) - Ciccio, Gabriele; Robert, Thomas; Smajda, Stanislas; Fahed, Robert; Desilles, Jean Philippe; Redjem, Hocine; Escalard, Simon; Mazighi, Mikael; Blanc, Raphael; Piotin, Michel
Abstract : Purpose: Self-expandable stents have broadened the spectrum of endovascular treatment of intracranial aneurysms. However, procedures involving double stenting in Y/X configurations carry a relatively high risk of procedural complications. The Neuroform ATLAS, the evolution of Neuroform EZ, is a nitinol self-expanding hybrid/open cell stent which can be delivered through a low profile 0.017 inch catheter. We present our experience in the treatment of intracranial aneurysms with this stent in Y and X configurations. Materials and methods: We prospectively maintained a database from consecutive patients who underwent double stent assisted coiling with the Neuroform ATLAS, from July 2015 to February 2019. Clinical and angiographic results were analyzed. Results: 55 patients harboring 55 bifurcation aneurysms were treated with double stenting: 52 'Y' configurations, 3 'X' configurations. Deployment was successful in all cases. Post-treatment control angiography showed complete occlusion in 33 cases (60%), neck remnant in 8 cases (14.5%), and incomplete occlusion in 14 cases (25.4%). The overall symptomatic periprocedural complication rate was 12.7%. 38 aneurysms underwent follow-up (69%, mean duration 16 months): 33 aneurysms (87%) were completely occluded, 3 aneurysms (8%) had a neck remnant, and 2 aneurysms (5%) were incompletely occluded. Conclusion: The Neuroform ATLAS is an effective device for treatment of bifurcation aneurysms, allowing good conformability, a high level of navigability, and easy mesh crossing to perform Y/X stenting procedures. The rate of procedural complications remains non-negligible, and an indication for a double stenting procedure should be carefully discussed in a multidisciplinary meeting.